If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 23 = m + -8 Combine like terms: -14 + 23 = 9 9 = m + -8 Reorder the terms: 9 = -8 + m Solving 9 = -8 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 9 + -1m = -8 + m + -1m Combine like terms: m + -1m = 0 9 + -1m = -8 + 0 9 + -1m = -8 Add '-9' to each side of the equation. 9 + -9 + -1m = -8 + -9 Combine like terms: 9 + -9 = 0 0 + -1m = -8 + -9 -1m = -8 + -9 Combine like terms: -8 + -9 = -17 -1m = -17 Divide each side by '-1'. m = 17 Simplifying m = 17
| -3(4x-1)=87 | | 4/9*3/8 | | 234^1/2+2=23 | | k+17=72 | | 3x-1=4x-11 | | 3y+0.5x-w=0 | | -48=3x | | 5/8(x-1/3)=5/12 | | m-15=-25 | | 6c+9c=-1 | | -9+3x=-30 | | 6c+9c=-1c | | 7.2(x-15.6)=-9 | | 8v-25=1v+80 | | 3y+0.5x-w=0fory | | (x/6)+(4/x-4)-(x/x-4)=0 | | 8+m=-11 | | 9x+5(x+7)=49 | | (a/6)+(4/a-4)-(a/a-4)=0 | | -5(4+2x)-(8x-12)=68 | | y^2+6y^1-2y=0 | | 1961614= | | 2y^4=50y^2 | | -6x-6=-18 | | 7-4(3m+2-3)-4=17 | | 2+7(3-4k)=31 | | 5m^2+m/7m | | 4(v+5)=-8 | | 7b(-6b-4)= | | 3d+16=d+18 | | 4/x-1/2x=-7/4 | | -4/7(x1/4)=3/7 |